THE EFFECT OF INVESTMENT AND PRODUCT DEVELOPMENT ON COMPANY SOLVENCY (CASE STUDY IN INDONESIAN PHARMACEUTICAL COMPANY PT X IN BANDUNG PERIOD 2016-2021) - Sularno, Agus; Sasmito, Paidi Wagiono; Budiantoro, Anandha (Journal of Management and Leadership, 2024)
Pharmaceutical businesses that do research must be aware of the essential aspects that influence innovation rates, R&D expenses, and the likelihood of success. The goal of the research was to look into the impact of product development elements, investment value, and alternative funding sources for research and product development activities on solvency. Simple linear regression and the Hypothesis Test (t-test) were used to assess the data. The results revealed that the optimal product selection strategy, investment obligations, and investment value will have a beneficial and substantial influence on the company's financial stability. The results presented have consequences for providing an analysis of the impact of investment in product research and development activities based on specific data on product development activities and company financial performance; and providing an overview of the impact of funding for research and product development activities in order to choose the best funding strategy.